Application of various methods in design for control of bed erosion and river modification aiding numerical simulation - Aref Kohzadi; Kamran Mohammadi; Afshin Eghbalzadeh (Journal of Applied Research in Water and Wastewater)
Erosion of the river bed and the drop in its level exposes all protective structures to damage and increase the level of the downstream bed which makes the river wider and causes the land of around it faces the flood risk. Therefore, determination of hydraulic parameters including effective stresses are very important. In this research, after calibrating the HEC-RAS numerical model, hydraulic simulation of the river was performed and the bed stress conditions were calculated. Then, the areas of the river bed that are subject to erosion were investigated using methods of critical shear stress, RBS index and critical unit discharge. Finally, stabilization structures for erosion control of the river bed were designed to modify the areas exposed to erosion. A reach of Karun River was investigated. A total of 14 erodible areas were identified along the main channel of the river. For these areas, the ripe rape, check dam, protective geobag cover and drop structures were designed. The D50 of ripe rap was found to be 11.02 cm. Maynard's formula (1989) in the design of ripe rap is in good agreement with the real conditions. The height of check dams was considered to be 1.8 m and D65 was 89 cm for all sections. The number of check dams in each interval was determined between 0 and 5. Bags with a volume of 1540 cm3 filled with sand were designed as a geobag cover. The height of the drops was considered to be 1.5 m for all sections, and the depth of the end sill, the length of the stilling basin and the height of the drop overflow were in the range of 0.02-0.29, 3.21-6.45 and 0.26-0.43 m, respectively.